A fog level detection method based on image HSV color histogram - Chunxue Liu; Xiaobo Lu; Saiping Ji; Wei Geng (2014 IEEE International Conference on Progress in Informatics and Computing, 2014)
As a direction in the development of computer vision, fog visibility detection is very important for traffic safety. Aiming at the visibility detection problem appearing in the highspeed road traffic, this paper proposes a fog level detection method based on image HSV color histogram. First, convert the background image color space from RGB color space to HSV color space. And then achieve the fog level detection by classifying fog weathers of different visibility level into different types using the image HSV color histogram features (including H, S, and V) in various weather conditions. The experimental results show that this method can make qualitative judgments on foggy days quickly and the qualitative detection results are relatively good.